Physical modelling for metal forming processes. (2017) - Krishnamurthy, B.; Bylya, O.; Davey, K.
Abstract: Physical modelling has a long established history for the investigation of metal forming and other manufacturing processes. In recent times however its place and importance has diminished somewhat as a direct consequence of advances made in numerical modelling techniques. This paper re-examines the place of physical modelling and by means of selected examples demonstrates the benefits of the approach. Physical modelling often provides an indirect representation of the physics under consideration and may often involve scaling and the use of cheaper substitute materials. A question posed that has in some respects contributed to the diminution of physical modelling is whether the physical model is representative of the physics involved. Related to this question is a new approach to scaled experimentation that has appeared in the recent literature. The new approach is founded on the scaling of space itself and although the idea that space expands and distorts is not new to physics (e.g. cosmology and general relativity) its application to physical modelling is considered completely novel. The scaling concept enables the physics of processes to be projected into a scaled space and vice versa, thus providing quantification of the validity of any physical model. This aspect fortifies a particular weakness in the physical modelling approach making its reappraisal particularly timely. Selected numerical and experimental trials are being designed to showcase and reveal the benefits, validity and renewed importance of physical modelling.